2008
DOI: 10.1590/s0102-695x2008000500003
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of essential oil of Citrus aurantium L. inhalation in rats

Abstract: RESUMO: "Efeitos comportamentais em ratos após inalação do óleo essencial de Citrus aurantium L.". O óleo essencial de laranja (OEL) e seus constituintes obtidos da Citrus aurantium L. (Rutaceae) têm despertado interesse pela sua ação sedativa e relaxante. No presente estudo, ratos previamente expostos à inalação do OEL nas concentrações de 1,0%; 2,5% e 5,0%, p/v, durante 7 minutos em caixas de acrílico, foram avaliados em dois modelos de ansiedade: labirinto em cruz elevado (LCE) e campo aberto. O OEL na conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 28 publications
3
46
1
6
Order By: Relevance
“…CT at all doses caused a significant reduction of ambulation of animals in the test of spontaneous movement after 0.5, 1 and 1.5 h of its administration in the doses of 100, 200 and 400 mg/kg, that corroborates with the hypothesis of the CT reduces the CNS activity. It was reported that reduction of the ambulation of the animals is characteristic of psychopharmacological drugs (Leite et al, 2008;Carlini, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…CT at all doses caused a significant reduction of ambulation of animals in the test of spontaneous movement after 0.5, 1 and 1.5 h of its administration in the doses of 100, 200 and 400 mg/kg, that corroborates with the hypothesis of the CT reduces the CNS activity. It was reported that reduction of the ambulation of the animals is characteristic of psychopharmacological drugs (Leite et al, 2008;Carlini, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The most noteworthy among these are C. x sinensis (Faturi et al, 2010) and C. x limon (Ceccarelli et al, 2004) in rats, and C. x latifolia (Gargano et al, 2008) and C. x aurantium (Carvalho-Freitas, Costa, 2002;Pultrini et al, 2006) in mice. Sedative and anxiolytic-like effects have been described for the EO obtained from the peel of Citrus x aurantium in rats and mice (Leite et al, 2008;Costa et al, 2013). However, the literature does not present reports of their anesthetic effects on fish.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that DMF may be a stimulatory to the CNS, since studies shows that reduction of the ambulation of the animals is characteristic of depressant drugs (Carlini, 2003;Freire et al, 2006;Leite et al, 2008;Quintans Júnior et al, 2008b).…”
Section: Discussionmentioning
confidence: 53%